Intramedullary bronchogenic cyst in the foramen magnum region accompanied with syringomyelia: A case report and literature review. Issue 5 (February 2019) - Chen, Fan; Marx, Sascha; Zhang, Chaochao; Cao, Junguo; Yu, Ying; Chen, Dawei
Abstract: Rationale: Bronchogenic cysts refer to congenital anomalies derived from the primitive foregut. Spinal bronchogenic cysts are uncommon entities, and those occurring in the intramedullary sites are extremely rare. Bronchogenic cysts involving the foramen magnum region have only been described in 2 cases; however, intramedullary bronchogenic cysts with syringomyelia have not yet been reported. Patient concerns: A 46-year-old woman presented with a 6-month history of pain in the posterior neck region and a 1-month history of numbness in the upper extremities. Neurological examination revealed a loss of sensation in bilateral upper extremities and sensory dissociation. Magnetic resonance imaging (MRI) showed an intramedullary cystic lesion in the foramen magnum region and syringomyelia. Diagnosis: Histopathological findings were consistent with a bronchogenic cyst. Interventions and outcomes: A surgical resection of the cystic lesion was performed via a posterior midline approach. Under neurophysiological monitoring, the cyst was punctured, yielding gelatinous liquid. The dorsal part of the cystic wall was removed. One month postoperatively, the symptoms were resolved completely. Three months after operation, MRI showed no recurrence of the cyst and the syringomyelia disappeared. Lessons: Intramedullary bronchogenic cysts with syringomyelia are extremely rare. Preoperative identification is challenging and definitive diagnosis depends on histopathological evidence. Timely surgical resection should be highlighted.